2018
DOI: 10.1590/1516-3180.2018.0019220318
|View full text |Cite
|
Sign up to set email alerts
|

Safety assessment of omeprazole use: a review

Abstract: BACKGROUND: Risks regarding hospital admission due to adverse drug reactions and drug interactions from use of omeprazole have been reported. The question guiding the present review was "Which adverse events occur in patients using omeprazole in a Food and Drug Administration-approved and/or off-label manner?" It was also proposed to evaluate the safety of use of omeprazole. DESIGN AND SETTING: Qualitative narrative review with critical evaluation, in a public university. METHODS: The PubMed, SCOPUS, LILACS, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…Proton pump inhibitors used for the treatment of gastroesophageal reflux, peptic ulcers and Zollenger–Ellison syndrome, such as a36 and a37 (omeprazole and lansoprazole, respectively), were reduced in very good yields, obtaining the corresponding sulfides b36 and b37 . These molecules, along with albendazole, b38 , a medicine used to treat parasitic infections, showed the compatibility of our method with nitrogen heterocycles, small carbamates and basic functional groups.…”
Section: Resultsmentioning
confidence: 99%
“…Proton pump inhibitors used for the treatment of gastroesophageal reflux, peptic ulcers and Zollenger–Ellison syndrome, such as a36 and a37 (omeprazole and lansoprazole, respectively), were reduced in very good yields, obtaining the corresponding sulfides b36 and b37 . These molecules, along with albendazole, b38 , a medicine used to treat parasitic infections, showed the compatibility of our method with nitrogen heterocycles, small carbamates and basic functional groups.…”
Section: Resultsmentioning
confidence: 99%
“…The additional relative reduction in the dispensing of omeprazole in Bavaria was probably due to the growing awareness of the suspected decrease in efficacy of the antiplatelet agent clopidogrel induced by omeprazole/esomeprazole [ 28 ] and the EMA safety communication. Conjoint use of clopidogrel and esomeprazole increased during this time, but the absolute proportions were very small.…”
Section: Discussionmentioning
confidence: 99%
“…Omeprazole is not known for SAEs at therapeutic doses during short-term treatments even though a recent review assessed the AEs reported in studies of different designs (e.g., clinical trials, cohort studies) and occurring at normal doses [22]. The usual maximum concentration observed after a single dose of omeprazole shows a large inter-individual variability range, for example, from 300 to 640 ng/mL after a single 40-mg dose of encapsulated enteric-coated granules [23].…”
Section: Discussionmentioning
confidence: 99%